Hubungan Antara Minat Baca Dengan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas IV SDN Kalegen 2 - Nugroho, Denis Agung (Prosiding University Research Colloquium, 2021)
This study aims to determine the relationship between reading interest and student learning outcomes in Indonesian language subjects for fourth grade students at SDN Kalegen 2 Bandongan, Magelang Regency. This research is a type of quantitative research with a correlational research design. Research subjects were taken using saturated sampling technique with a total sample of 21 students. Data collection techniques were carried out using a reading interest questionnaire, interviews on reading interest to students and documentation of student learning outcomes. The instrument validation test of the questionnaire used the product moment formula while the reliability test used the Cronbach alpha formula with the help of the SPSS for Windows V.26 program, the prerequisite test for normality and linearity, hypothesis testing using the non-parametric correlation Spearman rank analysis test technique because it does not meet the requirements to use parametric analysis test. The results showed that the correlation coefficient between the variable of reading interest and learning outcomes of fourth grade Indonesian students had a value of 0.002 < 0.05 (the significance value was smaller than the probability value). Meanwhile, the correlation figure is 0.645 in the high category and can be said to be positively related. So that there is a positive and significant relationship between reading interest and student learning outcomes in Indonesian class IV subjects. Thus the hypothesis is accepted.